PENINGKATAN RANK ALEXA MENGGUNAKAN METODE SEO UNTUK MENINGKATKAN WEB VISITOR PADA OFFICIAL SITE ILEARNING PLUS - Untung Rahardja; Ray Indra Taufik Wijaya; Endah Nirmala Dewi (Universitas Raharja, 2017)
Information Technology has gave major contribution to human life. Information has become the most important part of our lives. Online marketing is a phenomenon that appears in today's marketing world. This journal is written by reason of the presence of pressure from the high growth of the number of internet users, particularly in Indonesia. Overall of this paper will discuss the official site iLearning Plus, with any outlines some strategies that can increase the frequency of web visitor to the official site iLearning plus. The purpose of the strategy is to increase the popularity of official site iLearning Plus itself. Therefore it needs the right strategy to achieve this, one of them using the techniques of SEO (Search Engine Optimized ) with using Alexa benchmarks. In addition also explain about what methods are used in this journal such as literature review, mind maps, flowcharts, and the others. There is also a formulation of the problem and also the solution to solve the problem which has been accompanied by some evidence and the results that have been obtained. And the last, the conclusions of the results of research that addresses the entirety of this journal